NILAI FILOSOFIS-KULTURAL MUSIK KOLINTANG - Dominica Diniafiat; Ambrosius M. Loho (LPPM Universitas PGRI Adi Buana Surabaya, 2020)
This paper departs from the fact that Indonesia is a cultural superpower. Because of this existence, it is necessary to put forward more intensely various efforts that are not just a tale that is known, but at the same time we try to see the depth of all the cultural richness that exists. The values ​​of the culture need to be continually strived for, not only remembered, but known, and subsequently developed. Minahasa is an area that is an integral part of Indonesia. Minahasa also contains various kinds of cultural richness. And one of them is the traditional music art of Kolintang. Kolintang music is a typical Minahasan music that needs to be maintained and developed continuously to be recognized to all circles. However, the most important thing to know is the cultural values ​​in the music, if it can be used as a model in living together. Cultural values ​​are the key to learning in our lives. Therefore, we need to know those cultural values ​​for a proper and deep understanding.